2022
DOI: 10.1152/ajplung.00152.2021
|View full text |Cite
|
Sign up to set email alerts
|

Lung-kidney interactions and their role in chronic kidney disease-associated pulmonary diseases

Abstract: Chronic illnesses rarely present in a vacuum, devoid of other complications, and chronic kidney disease is hardly an exception. Comorbidities associated with chronic kidney disease lead to faster disease progression, expedited dialysis dependency, and a higher mortality rate. Although chronic kidney disease is most commonly accompanied by cardiovascular diseases and diabetes, there is clear crosstalk between the lungs and kidneys pH balance, phosphate metabolism, and immune system regulation. Our present under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 200 publications
0
7
0
Order By: Relevance
“…The mean age of CKD5-HD in Pakistan is 50 years, which is substantially lower than the average age in wealthy countries (16) . In contrast to our research, where the female-to-male ratio was 1:1, the average age in that investigation was about 45 years old.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The mean age of CKD5-HD in Pakistan is 50 years, which is substantially lower than the average age in wealthy countries (16) . In contrast to our research, where the female-to-male ratio was 1:1, the average age in that investigation was about 45 years old.…”
Section: Discussionmentioning
confidence: 83%
“…Another research indicated that 13.9 percent of 156 patients with chronic kidney disease had microcytic anemia (CKD stage not specified, existence of ESKD not ruled out), but did not offer a full description of IDA (16) . Anemia is a clinically important burden in CKD patients when the glomerular filtration rate (GFR) declines more often.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of the complex interaction between the kidneys and lungs has not been clearly elucidated, systemic inflammation and oxidative stress have been shown to play important roles [ 19 , 20 ]. Alge et al [ 21 ], who highlighted the interactions between the kidney and lungs in critically ill patients, reported that acute kidney injury (AKI) increased the generation of inflammatory cytokines, such as interleukin-6 (IL-6), causing increased trafficking of lymphocytes and neutrophils to the lungs, which contributed to the acute response distance syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing the general intake of fruits and vegetables is an effective approach to reducing the risk of asthma [12]. Signi cantly, lung diseases are interconnected with various systemic diseases and conditions, including heart disease and chronic kidney disease (CKD) [13,14].…”
Section: Introductionmentioning
confidence: 99%